Early modern literatures in North India: current research 2022–2024 - Nagasaki, Hiroko; Horstmann, Monika; Okita, Kiyokazu (Heidelberg Asian Studies Publishing (HASP), 2025)
This volume collects together the papers presented at the 14th session of the International Conferences on Early Modern Literatures in North India (ICEMLNI). In format, the conference represents a forum of current research without being restricted to a main theme. Nonetheless, the papers shared certain international academic issues and foci. Accordingly, grouped by categories, these are not rigid but fluid and thereby reflect the state of current academic debates. This introduction begins by delineating the widely shared topics, then briefly summarizes the individual contributions.
"14th International Conference on Early Modern Literatures in North India" - Acknowledgements
Keywords: Konferenzschrift; Bhakti-Dichtung; Literatur; Indien; Handschrift